Vision-Based Interfaces for Character-Based Text Entry: Comparison of Errors and Error Correction Properties of Eye Typing and Head Typing - Yulia Gizatdinova; Oleg Špakov; Outi Tuisku; Matthew Turk; Veikko Surakka (Advances in Human-Computer Interaction)
We examined two vision-based interfaces (VBIs) for performance and user experience during character-based text entry using an on-screen virtual keyboard. Head-based VBI uses head motion to steer the computer pointer and mouth-opening gestures to select the keyboard keys. Gaze-based VBI utilizes gaze for pointing at the keys and an adjustable dwell for key selection. The results showed that after three sessions (45 min of typing in total), able-bodied novice participants (N = 34) typed significantly slower yet yielded significantly more accurate text with head-based VBI with gaze-based VBIs. The analysis of errors and corrective actions relative to the spatial layout of the keyboard revealed a difference in the error correction behavior of the participants when typing using both interfaces. We estimated the error correction cost for both interfaces and suggested implications for the future use and improvement of VBIs for hands-free text entry.